Dysphagia Management in Head and Neck Cancers A Manual and Atlas (Springer Singapore, 2018)
Dysphagia and problems related to swallowing are common following treatment for head and neck cancers. Though there are books available on dysphagia management and associated neurological conditions, this is the only atlas that comprehensively discusses dysphagia related to the head and neck cancers. It comprises of 33 chapters divided into five sections. The initial chapters present the anatomy and physiology of swallowing and the pathophysiology of the dysphagia-related structures. It discusses assessment of dysphagia in detail, highlighting clinical and instrumental evaluations. Swallowing dysfunction related to common sub-site cancers and chemo-radiotherapy related dysphagia are explored individually. The book addresses direct and indirect swallowing therapy methods involving postures and exercises in a detailed yet simple manner to enable them to be incorporated in routine practice. It also covers topics like nutritional management, alternative feeding methods and unique problems associated with tracheostomy that have a great bearing on the day-to-day management of patients with dysphagia. The current status of the research and evidence- based management updates are also included. Additionally, where appropriate videos are included for a better understanding of the subject. Written and edited by experts in the field, the book is intended for clinicians treating head and neck cancer, head and neck surgeons, radiation oncologists, speech and swallowing therapy specialists and trainees in these fields.